Teachers’ Creativity in Student Literacy Habituation Islamic Elementary School in Banyumas Regency Indonesia - Sunhaji, Sunhaji; Pradana, Ade Eka; Dharin, Abu; Laela, Nur (Journal of Posthumanism, 2025)
The purpose of this study is to describe and analyze the creativity of teachers in the literacy habituation of students at Islamic Elementary School Ma’arif NU 1 Cilongok Banyumas. This study uses a descriptive qualitative method with observation, interview, and documentation data collection techniques. Data analysis is carried out by means of data collection, data reduction, and drawing conclusions. The results of this research are that teachers at Islamic Elementary School Ma’arif NU 1 Cilongok show high creativity in fostering a literacy culture. Creative and innovative literacy habituation has proven to be effective in increasing students’ interest and literacy skills. Islamic Elementary School Ma’arif NU 1 Cilongok has creative literacy programs such as reading 15 minutes before teaching and learning activities, literacy tree, reading corner, and optimization of display boards and wall magazines. Writing a reading summary/synopsis helps improve writing skills, express yourself, and develop creativity. Islamic Elementary School Ma’arif NU 1 Cilongok shows a strong commitment to fostering a culture of literacy and providing benefits for all student.